Offline signature verification using artificial neural network / Mohd Hafiz Hilmi Abdul Ghani - Abdul Ghani, Mohd Hafiz Hilmi (2012)
A person signature has many potential to be duplicated. The high risk of signature duplication happen nowadays that involve with high value of financial transaction. By using manual detection it is difficult to verify because of the similarity of duplication. Therefore, these problems need a mechanism that is capable to detect and protect their assets from being harmed and exploited by attackers. This project focuses on signature verification using Artificial Neural Network algorithm. The objective of this project is to develop a signature verification prototype system using Artificial Neural Network technique that is capable to verify whether the signature belongs to the same person or not.This project is using an offline method where the signature needs to be scanned first before entering the next phase in order to verify the signature. As a result of this project, the system successfully verifies the signature based on the Neural Network algorithm. It is hoped that this project will give benefits to other researcher in order to continue the same research in the same field